Australasian science incorporating Search (Hawksburn, Vic. : Control Publications, 1998)
'Multidisciplinary science magazine dedicated to science and technology in Australia'
Title from cover.
Merger of: Australasian science, and; Search (Sydney, N.S.W.)
Keywords: Science -- Australia -- Periodicals; Science -- New Zealand -- Periodicals; Technology -- Australia -- Periodicals; Technology -- New Zealand -- Periodicals; Electronic journals